Behaviors of hydrogen bonds formed by lignite and aromatic solvents in direct coal liquefaction: Combination analysis of density functional theory and experimental methods. (1st April 2020) - Hou, Ranran; Bai, Zongqing; Zheng, Hongyan; Feng, Zhihao; Ye, Donghong; Guo, Zhenxing; Kong, Lingxue; Bai, Jin; Li, Wen
Highlights: Hydrogen bonds significantly influence structure of solid products in direct coal liquefaction. Benzene is a stronger OH-π hydrogen bonds acceptor compared to tetralin. Benzene promotes lengthening of O–H bonds in when hydrogen bonds are formed. Benzene promotes decomposition of –OH and generation of aryl ether bonds in direct coal liquefaction. Abstract: Hydrogen bonds play a crucial role in thermal conversion of low rank coal, especially direct coal liquefaction (DCL) because of their wealthy abundance and great influence on generation of light products. Relative distribution of hydrogen bonds was evaluated with in-situ diffuse reflectance infrared Fourier transformation (DRIFT), while visualization analysis of hydrogen bonds (OH-π in particular) between coal and solvents were performed using density functional theory (DFT) and reduced density gradient (RDG) analysis. In terms of their effects, DCL experiments of demineralized Yunnan lignite (DeYN) with/without addition of benzene at 200, 250 and 300 °C were carried out, and oxygen-containing functional groups were investigated by solid-state 13 C NMR and in-situ DRIFT. Relative content of OH-π hydrogen bonds increased with temperature rising. Benzene is the stronger hydrogen bonds acceptor compared to tetralin (THN). Conclusions drawn from DCL experiments are consistent with DFT calculations. To be specific, benzene with mass concentration of 2% promotes cleavage of O–H bonds, carboxyl groups and the generation of aryl ether bonds, and the differences caused by benzene are intensified when DCL temperature rises.